Rising home values and Covid-19 case rates in Massachusetts (2020)
We explore whether housing displacement pressure could help explain place-based disparities in Massachusetts COVID-19 prevalence. We use qualitative data from the Healthy Neighborhoods Study to illustrate how rising and unaffordable housing costs are experienced by residents in municipalities disproportionately affected by COVID-19. We then predict municipal-level COVID-19 case rates as a function of home value increases and housing cost burden prevalence among low-income households, controlling for previously identified communitylevel risk factors. We find that housing value increase predicts higher COVID-19 case rates, but that associations are ameliorated in areas with higher home values. Qualitative data highlight crowding, “doubling up,” homelessness, and employment responses as mechanisms that might link housing displacement pressure to COVID-19 prevalence.